PENGARUH PENGGUNAAN MODEL PEMBELAJARAN ARTIKULASI TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMPN 21 PEKANBARU - Lina Hidayanti; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the low motivation of learning PPKnstudents at SMPN 21 Pekanbaru. The formulation of the problem of this research are:(1) Are there differences in learning motivation of men and women with the Articulationmodel in SMPN 21 Pekanbaru, (2) Are there differences in learning motivation of menand women with conventional models in SMPN 21 Pekanbaru, (3 ) Is there a differencebetween learning motivation that is taught using Articulation and Conventional models,(4) Is There a Significant Effect on the Use of Articulation Learning Models onLearning Motivation of men and women. The study aims to determine the effect of theArticulation Learning Model on Student Learning Motivation at PPPN 21 Pekanbaru.The study was conducted at SMPN 21 Pekanbaru in February 2020. This research wasan experimental quantitative descriptive study. With a population of eighth gradestudents in Pekanbaru 21 Junior High School and Samples using the Random Samplingtechnique, the sample is students of class VIII 7 (experimental class) and class VIII 6(control class) which is tested for homogeneity. Based on the research results, theformulation of the problem (1) there are differences in learning motivation of men andwomen using the Articulation Learning model (2) there are differences in learningmotivation of conventional methods (3) there is a difference between the articulationand conventional models and (4) there is a significant influence. Then the hypothesisthat says there is an influence of the use of the articulation learning model on thelearning motivation of students in class VIII in SMP 21 Pekanbaru,